Anticancer activities of anthocyanin extract from genotyped Solanum tuberosum L. "Vitelotte". (December 2015) - Bontempo, Paola; De Masi, Luigi; Carafa, Vincenzo; Rigano, Daniela; Scisciola, Lucia; Iside, Concetta; Grassi, Roberto; Molinari, Anna Maria; Aversano, Riccardo; Nebbioso, Angela; Carputo, Domenico; Altucci, Lucia
Highlights: Molecular genotyping of Vitelotte potato was identified promoting the use of this genetic resource by plant breeders. Molecular analyses of anthocyanin action in cancer revealed modulation of cell cycle regulators. Anthocyanin extract inhibited Akt-mTOR signalling inducing maturation of acute myeloid leukaemia cells. Abstract: The action of anthocyanins contained in the Vitelotte potato ( Solanum tuberosum L.) in both breast and haematological cancers were investigated. The biomedical activities of anthocyanin extract derived from the Vitelotte cultivar were determined. Molecular genotyping was performed to properly identify this outstanding genotype in comparison to other potato varieties and to promote the utilization of this genetic resource by plant breeders. Furthermore, cellular and molecular characterization of the action of anthocyanin extract in cancer cells revealed that modulation of cell cycle regulators occurs upon treatment. As well as inducing apoptotic players such as TRAIL in cancer systems, anthocyanin extract inhibited Akt-mTOR signalling thereby inducing maturation of acute myeloid leukaemia cells. These results are of interest in view of the impact on food consumption and as functional food components on potential cancer treatment and prevention.